COMPETITIVE ADVANTAGE STRATEGY BASED ON PRODUCT DIFFERENTIATION: A QUALITATIVE CASE STUDY OF A BAKERY MSME IN BANDAR LAMPUNG, INDONESIA - Adi Priyatna; Agus Purnomo (PT. Jurnal Center Indonesia Publisher, 2026)
Small and Medium Enterprises (SMEs) play a crucial role in strengthening local and national economies, particularly in developing countries such as Indonesia. Increasing market competition, digital transformation, and changing consumer preferences have forced SMEs to continuously develop competitive strategies in order to survive and grow sustainably. This study aims to analyze a competitive advantage strategy based on product differentiation implemented by Roti Kaisar, a bakery micro-enterprise located in Kemiling District, Bandar Lampung. Using a descriptive qualitative approach, data were collected through in-depth interviews, direct observation, and documentation. SWOT analysis was employed to identify internal strengths and weaknesses as well as external opportunities and threats affecting business competitiveness. The findings reveal that Roti Kaisar’s competitive advantage is driven by consistent product quality, independent production processes, diverse product variations, and strong customer loyalty. However, the enterprise also faces challenges such as limited production capacity, suboptimal digital marketing, and fluctuating raw material prices. The results indicate that product differentiation strategies—supported by innovation, improved packaging, digital marketing utilization, and local brand strengthening are effective in enhancing competitive positioning and supporting sustainable business growth for bakery MSMEs.